First record of Nevrorthidae from Slovenia - Jones, Joshua R. (Acta entomologica slovenica (Ljubljana), 2009)
Nevrorthus apatelios H. Aspöck, U. Aspöck et Hölzel, 1977 is recorded for the first time from Slovenia. The finding on the southwest slopes of the eastern Julian Alps represents the northernmost record for the family in Europe. A list of known localities for N. apatelios is provided in an appendix.
Keywords: entomologija; entomology; fauna; favna; najdbe; new records; Slovenia; Slovenija